INTEGRATION OF DIGITAL TECHNOLOGIES INTO THE PROFESSIONAL ACTIVITIES OF PRESCHOOL TEACHERS - Vinnik, Тетяна (Journal of Information Technologies in Education (ITE), 2021)
The purpose of the article is to analyze and describe the results of the study of the current state of the introduction of digital technologies in preschool education, in particular the available means of digital technologies for preschool education, the level of ICT competence of educators, the level of integration of digital technologies in the educational process, ways to apply digital technologies in practice. The results showed that most educators are well aware of the use of educational ICTs. However, the level of integration of ICTs into the educational process is still at a low level. Most educators are ordinary users and use ICT for their own needs, and not for direct support of the educational process of preschool education. In addition, the effective integration of ICTs into the professional activities of educators is hindered by insufficient training, lack of modern equipment and time constraints. Although educators were positive about the use of digital technologies in preschool education, respondents used ICT on a limited scale, mainly for watching videos and listening to music. Observations and interviews with caregivers prove that ICTs can improve the practice of preschool education, providing many additional opportunities to enrich and transform the educational process. The study shows that ICTs in preschool institutions are used in various directions: as a tool for enriching current practices; as a cultural intermediary; as a way of entertainment and development of children; as a means of communication and documentation. In addition, considering the values and attitudes of educators to ICT in preschool age, the article describes the position of educators who believe that ICT is not desirable to use in the education of preschool children. The results of this study can be useful for conducting discussions about any innovations in preschool education, in particular, the introduction of new technologies.